Violence in America's schools: understanding, prevention and responses - Thomas, R. Murray (Praeger, 2006)
Varieties of school violence -- Deadly weapons -- Threats of violence -- Fighting -- Child abuse -- Sexual abuse -- Bullying and hazing -- Vandalism -- Theft -- Disruptive behavior -- Planning treatments